Predictors of symptom severity and treatment attendance amongst rape and sexual assault survivors attending a Cape Town crisis counselling service - Dollman, Nicola (Department of Psychology, 2019)
Despite the prevalence of rape in South Africa and its association with a high risk of mental health difficulties, little research has examined the specific predictors of post-rape symptom severity or counselling retention rates of treatment-seeking rape survivors. This mixed methods study aimed to investigate predictors of symptom severity and treatment attendance amongst rape survivors attending a crisis counselling service in Cape Town. The quantitative phase of the research was comprised of a retrospective chart review of 482 intake files at three Rape Crisis counselling centres in Cape Town between 2012 and 2016. The qualitative phase involved four focus group interviews with 25 Rape Crisis counsellors at these three counselling centres. Quantitative data were analysed using bivariate statistics, a multiple linear regression and a zero-truncated negative binomial. Multiple linear regression analysis revealed that being English-speaking, reporting being raped (as opposed to reporting a sexual assault or attempted rape), and rape by an unknown perpetrator were associated with increased symptom severity. A zero-truncated negative binomial revealed that increased symptom severity, being male and identifying as a race other than black or coloured were associated with longer time in treatment. Counsellors perceived lower reported symptom severity to be influenced by clients’ ability to identify symptoms, while poverty, poor social support, experiences of other trauma and knowing the perpetrator were perceived to increase symptom severity. Being a survivor of drug-alcohol facilitated rape/incapacitated rape and having practical obstacles to attending treatment were perceived by counsellors to result in shorter treatment attendance. Motivation for attending counselling was also perceived to influence length of attendance. There was both convergence and divergence between the quantitative and qualitative results. The implications of the findings for future research and delivering counselling to rape survivors are discussed. Keywords: Rape; sexual assault; symptom severity; treatment attendance.